Interleukin-6 and total antioxidant capacity levels following N-acetylcysteine and a combination nutraceutical intervention in a randomised controlled trial for bipolar disorder. Issue 6 (30th December 2020) - Bortolasci, C.C.; Voigt, C.; Turner, A.; Mohebbi, M.; Gray, L.; Dodd, S.; Walder, K.; Berk, M.; Cotton, S.M.; Malhi, G.S.; Ng, C.H.; Dowling, N.; et al.
Abstract: Objective: The aims of this study were to evaluate changes in inflammatory and oxidative stress levels following treatment with N -acetylcysteine (NAC) or mitochondrial-enhancing agents (CT), and to assess the how these changes may predict and/or moderate clinical outcomes primarily the Montgomery-Åsberg Depression Rating Scale (MADRS). Methods: This study involved secondary analysis of a placebo-controlled randomised trial ( n = 163). Serum samples were collected at baseline and week 16 of the clinical trial to determine changes in Interleukin-6 (IL-6) and total antioxidant capacity (TAC) following adjunctive CT and/or NAC treatment, and to explore the predictability of the outcome or moderator effects of these markers. Results: In the NAC-treated group, no difference was observed in serum IL-6 and TAC levels after 16 weeks of treatment with NAC or CT. However, results from a moderator analysis showed that in the CT group, lower IL-6 levels at baseline was a significant moderator of MADRS χ 2 (df) = 4.90, p = 0.027) and Clinical Global Impression-Improvement (CGI-I, χ 2 (df) = 6.28 p = 0.012). In addition, IL-6 was a non-specific but significant predictor of functioning (based on the Social and Occupational Functioning Assessment Scale (SOFAS)), indicating that individuals with higher IL-6 levels at baseline had a greater improvement on SOFAS regardless of their treatment ( p = 0.023). Conclusion: Participants with lower IL-6 levels at baseline had a better response to the adjunctive treatment with the mitochondrial-enhancing agents in terms of improvements in MADRS and CGI-I outcomes.